EFFECT OF THINK-PAIR-SHARE INSTRUCTIONAL STRATEGY ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN BIOLOGY IN ANAMBRA EAST LOCAL GOVERNMENT AREA, ANAMBRA STATE (UNIZIK Journal of STM Education, 2019)
This study investigated the effect of think–pair-share instructional strategy on secondary school students’ academic achievement in Biology. Two research questions and three hypotheses guided the study. The study adopted a quasi-experimental design. The sample was made up of 73 (38 males and 35 females) senior secondary class two (SS2) Biology students, from two public co-educational schools in Anambra East Local Government Area of Anambra State. The experimental group had 40 students (23 males and 17 females) while the control group had 33 students (15 males and 18 females).  Purposive sampling technique was used to select the sample. Biology Achievement Test (BAT) was used for data collection. The test was administered once and the reliability index of 0.95 was established on BAT using Kuder Richardson Formula 20. The experimental group was taught using think-pair-share instructional strategy while the control group was taught using conventional method. Mean and standard deviation were used to answer the research questions while Analysis of Covariance was used to test the null hypotheses at 0.05 level of significance. The result showed that a significant difference exists in the mean academic achievement scores of students in Biology in favour of the experimental group. There was no significant difference in the mean academic achievement scores of male and female students taught Biology using think–pair-share instructional strategy. Based on the findings, the researcher recommended among others that biology teachers should adopt the use of think-pair- share instructional strategy in order to improve both male and female students’ academic achievement in biology.
Keywords: Think-pair-share; academic achievement; biology students